Florida Subtropical Peaches: Production Practices - Mercy Olmstead; Jose Chaparro; Jeffrey G. Williamson; Robert Rouse; Russell Mizell; Philip Harmon; James Ferguson (EDIS)
Subtropical peach production includes many practices, such as site selection, orchard design, and disease, weed, and insect management through to harvest. Florida’s subtropical climate allows growers to harvest their crops early, but it creates challenges for the long postharvest growing season. This 14-page fact sheet covers the breadth of topics related to subtropical peach production, including a monthly timeline of recommended practices. Written by M. Olmstead, J. Chaparro, J. G. Williamson, R. Rouse, R. Mizell, P. Harmon, and J. Ferguson, and published by the UF Department of Horticultural Sciences, August 2013.